Rabbit model of tracheal stenosis using cylindrical diffuser. Issue 4 (16th November 2016) - Lee, Hyoung Shin; Kim, Sung Won; Oak, Chulho; Kang, Hyun Wook; Oh, Junghwan; Jung, Min Jung; Kim, Sung Bin; Won, Jun Hee; Lee, Kang Dae
Abstract : Background and Objective: Variable methods of animal model have been introduced to develop tracheal stenosis. However, none of the prior models allow for predictable determination of the grade of stenosis. This study sought to establish an animal model of tracheal stenosis by using a cylindrical diffuser and to evaluate the feasibility of a reproducible model. Study Design/Materials and Methods: A cylindrical diffuser was developed to have a 5 mm active segment to emit laser light circumferentially. Twenty one New Zealand white rabbits were enrolled in this study. The cylindrical diffuser was inserted transorally under bronchoscopic view and the diffused light was delivered to tracheal mucosa 2 cm below the level of vocal cord. Input power of irradiation was 10 W, 5 seconds in group A ( n = 7), 10 W, 7 seconds in group B ( n = 7), and 8 W, 5 seconds in group C ( n = 7). The degree of tracheal stenosis was observed weekly and the rabbits were euthanized 4 weeks after the laser irradiation. Results: The degree of stenosis in group B (90–98%) was significantly larger than that of group A (75–92%) ( P = 0.004), while degree in group C (24–35%) was significantly smaller than that of group A ( P < 0.001). Two rabbits of group A were euthanized at 3 weeks due to costal retraction. In group B, six rabbits died within 3 weeks after laser irradiation due to severe tracheal stenosis and tracheal malacia, while one rabbit was euthanized 16 days after the irradiation. All rabbits in group C survived up to 4 weeks. Survival between three groups showed significant difference ( P = 0.001). Conclusion: The degree of stenosis was significantly different according to the delivered optical energy to tracheal mucosa. Therefore, the proposed model may be used in animal studies to emulate variable grades of tracheal stenosis. Lasers Surg. Med. 49:372–379, 2017. © 2016 Wiley Periodicals, Inc.